Harmonized Datasets of microbiological parameters from a French national-scale soil monitoring survey - Aurélien Cottin; Samuel Dequiedt; Christophe Djemiel; Nicolas Chemidlin Prévost-Bouré; Julie Tripied; Mélanie Lelièvre; Lucie Terreau; Tiffanie Régnier; Battle Karimi; Claudy Jolivet; Antonio Bispo; Nicolas Saby; et al. (Scientific Data)
Abstract Microbiological datasets and associated environmental parameters from the French soil quality monitoring network (RMQS) offer an opportunity for long-term and large-scale soil quality monitoring. Soils supply important ecosystem services e.g. carbon dynamics/storage or mineral element recycling, supported by the soil microbial diversity (bacteria, archaea and fungi). Based on the 2,240 sites of the 2000–2015 RMQS, molecular tools were applied to characterize soil microbiota. Soil DNA analysis yielded molecular microbial biomass for 2,168 sites, bacterial and fungal qPCR for 2,073 sites, and high-throughput amplicon sequencing of targeted 16S rDNA bacterial and archaeal genes for 1,842 sites. All these datasets were partially or completely unavailable, so raw results files from RMQS microbiological studies were harmonized and published in a Dataverse repository to facilitate their reusability. Altogether, these datasets allow for in-depth studies of soil microbial ecology and biogeography, and will be updated with fungal datasets and the second currently ongoing monitoring campaign (2016–2027).